Fabrication and characterization of affordable hydrophobic ceramic hollow fibre membrane for contacting processes - Abdulhameed, Mohammed Abdulmunem; Othman, Mohd Hafiz Dzarfan; Al Joda, Haider Nadhom Azziz; Ismail, Ahmad Fauzi; Matsuura, Takeshi; Harun, Zawati; A. Rahman, Mukhlis; Puteh, Mohd Hafiz; Jaafar, Juhana (Springer Nature, 2017)
Affordable hydrophobic hollow fibre membranes were prepared using kaolin and alumina based ceramic powders via a combined phase inversion and sintering technique, followed by a grafting with fluoroalkylsilane (FAS). The crux of the matter in this paper is to study the changes in the properties of the hollow fibre membranes (gas permeation, mechanical strength, pore size, porosity, tortuosity, morphology, and contact angle) by the addition of alumina (Al2O3) to the pure kaolin with mono or multiparticle sizes. By varying the overall loading and particle size of alumina addition, different morphologies of the membranes were obtained due to the differences in the path lengths during phase inversion process for each solvent and nonsolvent exchange. The successful grafting with FAS was evidenced by the increase in contact angle from nearly equal to zero degree before grafting to 140° after grafting. Kaolin–alumina-4, one of the hollow fibres fabricated in this work, achieved a mean pore size of 0.25 µm with the bending strength of 96.4 MPa and high nitrogen permeance of 2.3×105 mol·m2 ·Pa1 ·s1 , which makes the hollow fibre most suitable for the membrane contactor application